2017
DOI: 10.1016/j.jotr.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anaesthesia on Mobilisation following Hip Fracture Surgery: An Observational Study

Abstract: Background Anaesthetic technique can influence mortality and morbidity following hip fracture surgery. However, its influence on postoperative mobilisation is not clear. In this study, we evaluated the influence of anaesthetic technique on postoperative mobilisation. Methods In this prospective observational study, we included all consecutive patients who underwent surgery for hip fracture between 1 January 2012 and 31 December 2013 at our institution. Any patients who died prior to mobilisation or who could n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, one RCT found that patients given RA were slower to be discharged from PACU (mean time to discharge GA 35.04 min (SD 3.39) vs RA 41.26 min (SD 8.37), p=0.001) 111. No significant differences were found in the non-randomised studies regarding time to ambulation,103 112 113 walking speed,62 time to rise from chair,42 mean Barthel’s score73 or ambulation at 3, 6 and 12 months post surgery 45 105. Overall results may suggest a small benefit from RA for immediate post-anaesthetic mobilisation.…”
Section: Resultsmentioning
confidence: 88%
“…However, one RCT found that patients given RA were slower to be discharged from PACU (mean time to discharge GA 35.04 min (SD 3.39) vs RA 41.26 min (SD 8.37), p=0.001) 111. No significant differences were found in the non-randomised studies regarding time to ambulation,103 112 113 walking speed,62 time to rise from chair,42 mean Barthel’s score73 or ambulation at 3, 6 and 12 months post surgery 45 105. Overall results may suggest a small benefit from RA for immediate post-anaesthetic mobilisation.…”
Section: Resultsmentioning
confidence: 88%